Strategi branding bimbingan belajar Omah Sinau di Sekolah Dasar - Fadilah, Nila; Shifah, Layyinatus; Yulian, Fatkhiyah Nur; Zuhriyah, Indah Aminatuz (Maliki Interdisciplinary Journal, 2024)
Along with the era of globalization that continues to increase. Competition in various aspects of life continues to occur. Many people are enthusiastic about building educational institutions, both formal and informal. This shows that education is not only held in formal schools but can be held outside schools such as non-formal education in the form of tutoring or courses. Therefore, tutoring institutions also have a strong role as a form of community participation in realizing educational ideals. It also functions as a substitute, addition, or complement to formal education. The purpose of this research is (1) to find out the strategies used to attract students' interest in participating in tutoring at Omah Sinau. (2) knowing that the branding strategy has an influence on Omah Sinau's tutoring to increase the number of students with the specified targets. The research used is a qualitative research method. The data collection that researchers used was observation and interviews. The results of the research show that the branding strategy carried out by Omah Sinau Tutoring has a big influence on students' choices in choosing a place for tutoring or private tutoring.